2022
DOI: 10.1038/s41375-022-01696-w
|View full text |Cite
|
Sign up to set email alerts
|

METTL3 mediates chemoresistance by enhancing AML homing and engraftment via ITGA4

Abstract: Chemoresistant leukemia relapse is one of the most common causes of death for acute myeloid leukemia (AML) patients and the homing/engraftment in bone marrow (BM) are crucial steps for AML cells to acquire chemoresistance by interacting with stromal cell components. No crosstalk between m6A modification and homing/engraftment has been reported. Here, we performed comprehensive high-throughput analyses, including RNA sequencing of CR (complete remission) and relapsed AML patients, and reverse-phase protein arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Recent studies have confirmed that METTL3 is abnormally overexpressed in AML and is closely related to the occurrence and development of AML [6]. Previous studies by our group found that METTL3 also plays an important role in the chemoresistance of AML [7]. A METTL3 inhibitor has shown promising therapeutic effects in AML animal models [8].…”
Section: Introductionmentioning
confidence: 71%
“…Recent studies have confirmed that METTL3 is abnormally overexpressed in AML and is closely related to the occurrence and development of AML [6]. Previous studies by our group found that METTL3 also plays an important role in the chemoresistance of AML [7]. A METTL3 inhibitor has shown promising therapeutic effects in AML animal models [8].…”
Section: Introductionmentioning
confidence: 71%
“…METTL3 mediates resistance to other chemotherapeutic drugs, including platinum-etoposide in Small Cell Lung Cancer (SCLC), doxorubicin, 5-fluorouracil (5-FU), and oxaliplatin in CRC, Idarubicin in AML, and docetaxel in breast cancer. 114,[118][119][120][121][122] Downregulation of METTL3 also associates with resistance to daunorubicin and cytarabine in AML. 114 The m6A erasers FTO and ALKBH5 also mediate chemoresistance in cancer.…”
Section: Players In Chemoresistancementioning
confidence: 99%
“…METTL3-mediated m6A modification induces the chemo-resistance in acute myeloid leukemia (AML) cells by increasing the stability of integrin subunit alpha 4 (ITGA4) mRNA [ 130 ].…”
Section: Roles Of Rna Methylases and M6a Binding Proteins In Anticanc...mentioning
confidence: 99%